Лідерські якості в структурі складових компетентностей менеджерів - Яценко, Ольга Миколаївна (ВД "Гельветика", 2016)
Проаналізовано думки науковців, стосовно компетентнісного підходу в освіті. Досліджено теоретичні питання аналізу основних компетентностей майбутніх менеджерів. Обґрунтовано певний перелік компетентностей, що завдяки сформованим лідерським якостям, дозволять успішно працювати у конкурентному середовищі. Надано приклад вимог до основних функцій менеджера з позиції успішного керівника-лідера із вже сформованими лідерськими якостями. Запропоновано модель взаємозалежності ефективної діяльності організації від сформованих основних компетентностей та лідерських якостей майбутніх менеджерів.

Research associates thoughts are analyzed regarding the competent approach in education. Theoretical matters are researched of the the main competency of the future managers. Specific list of competency is justified which because of established leadership qualities will help to work successfully in the competitive environment. The example of requirements regarding the main managers functions from the point of the successful manager-leader with already established leadership qualities is provided. The model of mutual dependence of effective organization operation from the established main competencies and leadership qualities of the future managers is suggested.
Leadership qualities in the structure of the manager’s compitence construction
Keywords: менеджери; компетентність; лідерські якості; організація; управління; managers; competence; leadership qualities; organization; management